The role of membranous urethral afferent autonomic innervation in the continence mechanism after nerve sparing radical prostatectomy: a clinical and prospective study - Catarin, Marcos Vinicius Guarnieri; Manzano, Gilberto Mastrocola; Nóbrega, João A. M.; Almeida, Fernando G.; Srougi, Miguel; Bruschini, Homero (Wolters Kluwer, 2008)
Purpose: We evaluated the somatic and autonomic innervation of the pelvic floor and rhabdosphincter before and after nerve sparing radical retropubic prostatectomy using neurophysiological tests and correlated findings with clinical parameters and urinary continence. Materials and Methods: From February 2003 to October 2005, 46 patients with prostate cancer were enrolled in a controlled, prospective study. Patients were evaluated before and 6 months after nerve sparing radical retropubic prostatectomy using the UCLA-PCI urinary function domain and neurophysiological tests, including somatosensory evoked potential, and the pudendo-urethral, pudendo-anal and urethro-anal reflexes. Clinical parameters and urinary continence were correlated with afferent and efferent innervation of the membranous urethra and pelvic floor. We used strict criteria to define urinary continence as complete dryness with no leakage at all, not requiring any pads or diapers and with a UCLA-PCI score of 500. Patients with a sporadic drop of leakage, requiring up to 1 pad daily, were defined as having occasional urinary leakage. Results: Two patients were excluded from study due to urethral stricture postoperatively. We evaluated 44 patients within 6 months after surgery. The pudendo-anal and pudendo-urethral reflexes were unchanged postoperatively (p = 0.93 and 0.09, respectively), demonstrating that afferent and efferent pudendal innervation to this pelvic region was not affected by the surgery. Autonomic afferent denervation of the membranous urethral mucosa was found in 34 patients (77.3%), as demonstrated by a postoperative increase in the urethro-anal reflex sensory threshold and urethro-anal reflex latency (p <0.001 and 0.0007, respectively). Six of the 44 patients used pads. One patient with more severe leakage required 3 pads daily and 23 showed urinary leakage, including 5 who needed 1 pad per day and 18 who did not wear pads. Afferent autonomic denervation at the membranous urethral mucosa was found in 91.7% of patients with urinary leakage. Of 10 patients with preserved urethro-anal reflex latency 80% were continent. Conclusions: Sensory and motor pudendal innervation to this specific pelvic region did not change after nerve sparing radical retropubic prostatectomy. Significant autonomic afferent denervation of the membranous urethral mucosa was present in most patients postoperatively. Impaired membranous urethral sensitivity seemed to be associated with urinary incontinence, particularly in patients with occasional urinary leakage. Damage to the afferent autonomic innervation may have a role in the continence mechanism after nerve sparing radical retropubic prostatectomy.
Keywords: Innervation; Prostate; Prostatectomy; Prostatic neoplasms; Reflex; Adult; Aged; Autonomic denervation; Autonomic innervation; Clinical article; Clinical trial; Controlled study; Evoked somatosensory response; Human; Latent period; Male; Neurophysiology; Pelvis floor; Perceptive threshold; Priority journal; Prostate cancer; Urethra stricture; Urinary tract function; Urine incontinence; Adult; Aged; Humans; Male; Middle aged; Neurons, afferent; Prospective studies; Prostatectomy; Urethra; Urinary Incontinence